Analisis Peluang dan Tantangan Perdagangan Elektronik Eksport dan Import Indonesia pada Negara Asia Tahun 2025 - Virginia Putri Angelita (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study analyzes the opportunities, threats, impacts of tariff increases, and solutions in Indonesia's electronic sector trade with Asian countries in 2025. The data shows that Indonesia experiences a significant trade deficit, where imports of electronic goods are much higher than exports. This condition indicates a strong dependence on foreign products, particularly from major producers such as China, Japan, and South Korea. Despite these challenges, Indonesia has opportunities to develop its role in the global supply chain, especially in the production of electronic components. However, several threats remain, including intense competition, low added value of exports, and limited technological capability. Furthermore, the implementation of higher import tariffs by Asian countries can reduce Indonesia's export performance and worsen the trade balance. To address these issues, strategic efforts are required, such as strengthening domestic industries, improving human resources, expanding export markets, and enhancing international trade cooperation. With appropriate policies and development strategies, Indonesia can improve its competitiveness and position in the electronic trade sector in Asia.